Adölesanlarda Meyve ve Sebze Tüketimi Değişim Süreci Ölçeği Türkçe Formunun Güvenilirlik ve Geçerliliği - (:unkn) unknown (My University, 2016)
Amaç: Bu araştırmanın amacı, DiNoia ve arkadaşları tarafından geliştirilen Meyve ve Sebze Tüketimi Değişim Süreci Ölçeği (MSTDSÖ)'ni Türkçe'ye uyarlamak ve ölçeğin güvenirlik ve geçerlik analizlerini yapmaktır.Yöntem: Araştırmanın evrenini İstanbul ili Üsküdar ilçesinde bulunan dört kamu ilköğretim okulunun 6-8. sınıf öğrencileri (n=1516) oluşturdu. Veriler Mart-Mayıs 2011 tarihleri arasında, tanıtıcı bilgi formu ve Meyve ve Sebze Tüketimi Değişim Süreci Ölçeği ile toplandı. Ölçeğin güvenilirliği, iç tutarlılık ve test-tekrar test ile, geçerliliği kapsam geçerliği ve yapı geçerliliği ile değerlendirildi. Yapı geçerliği doğrulayıcı faktör analizi, açımlayıcı faktör analizi ile test edildi. Bulgular: Tüm ölçek için iç tutarlılık güverlirliği Cronbach's Alfa katsayısı .91, bilişsel süreçler alt boyutu için .79, davranışsal süreçler için .90 bulundu.Ölçek alt boyut madde toplam korelasyonları, pozitif yönde ve istatistiksel olarak ileri düzeyde anlamlıydı (p<.001). Test-tekrar test güvenirliği korelasyon değeri . 81 bulundu. Geçerlik bulguları; kapsam geçerliği indeksi .94 bulundu. Açımlayıcı faktör analizi ölçeğin orijinali ile uyumlu faktör yapısına sahip olduğunu gösterdi.Doğrulayıcı Faktör Analizi ve uyum iyiliği değeri (x2/sd ve SRMR) kabul edilebilir değerde olduğunu ve orjinal faktör yapısının doğrulandığını gösterdi. Sonuç: Meyve sebze tüketimi değişim süreci ölçeğinin Türkçe formu yüksek güvenirlik, iyi kapsam ve yapı geçerliğine sahiptir

Objective:The aim of this research was to examine the psychometric properties of the Turkish version of the Processes of Change Scale for fruit and vegetable consumption in adolescents. Methods: The study population consisted of 6th - 8th grade students (n=1516) in the second tier of the four elementary public education system in the district of Üsküdar/Istanbul. Data were collected March to May 2011, using by "socio demographic questionaire" and "The processes of change Scale" for vegetable and fruit consumption in adolescents. The scale reliability was evaluated in terms of internal consistency reliability and testretest reliability. Construct validity of the scales was assessed by using exploratory factor analysis, confirmatory factor analysis. Validity was assessed in terms of content and construct validity. Result: The all scale, internal consistency Cronbach's alpha coefficient was found .91, cognitive processes subscale .79, behavioral processes .90. Scale subscale item-total score correlations was found positive and statistically significant (p <.001). Test-retest reliability correlation was .81, found. Validity findings; content validity index was over .94 for all the scale and showed that good content. Exploratory factor analysis showed that the factor structure of the original compatible with all scales. Confirmatory Factor Analysis and goodness of fit value is (x2/sd ve SRMR) within acceptable values, and showed that the factor structure of the original verification. Conclusion: The consumption of fruit and vegetables, the process of change scale, the Turkish form of high reliability, has good content and construct validity
Reliability and Validity of the Turkish Version of the Process of Change Scale for Fruit and Vegetable Consumption in Adolescents
Keywords: Sağlık Bilimleri ve Hizmetleri